IL-1β Promotes a New Function of DNase I as a Transcription Factor for the Fas Receptor Gene - Thiyagarajan, Dhivya; Pedersen, Hege L.; Seredkina, Natalya; Horvei, Kjersti D.; Arranz, Lorena; Sonneveld, Ramon; Nijenhuis, Tom; van der Vlag, Johan; Rekvig, Ole P. (Frontiers in Cell and Developmental Biology, 2018)
Recently we described that endonuclease inactive DNase I translocated into the nucleus in response to increased endogenous IL-1β expression. Here, we demonstrate impact and function of nuclear DNase I in tubular cells. Effect of cytokines on expression level and nuclear localisation of DNase I and corresponding levels of Fas receptor (FasR) and IL-1β were determined by confocal microscopy, qPCR and western blot analyses, in presence or absence of siRNA against IL-1β and DNase I mRNA. Nuclear DNase I bound to the FAS promotor region as determined by chromatin immuno-precipitation analysis. Data demonstrate that translocation of DNase I depended on endogenous de novo-expressed IL-1β; nuclear DNase I bound FAS DNA; FasR expression increased after translocation of DNase I; interaction of exogenous Fas ligand (FasL) with upregulated FasR induced apoptosis in human tubular cells stimulated with TNFα. Thus, translocated DNase I most probably binds the promoter region of the FAS gene and function as a transcription factor for FasR. By enhancing FasR expression, DNase I not only executes chromatin degradation during apoptosis, but also primes the cells for apoptosis.